Варшаўскі перыяд жыцця Я. Ф. Карскага і лёс яго бібліятэкі - Shved, Viachaslau (Przegląd Środkowo-Wschodni, 2020)
In the fi rst part of the article, the author tells about the Warsaw period of Karsky’s life: his teaching, scientifi c and social activities. The second part of the article is devoted to the fate of the Warsaw library. The author writes about putting the library of Karsky in the deposit of the Library of the Warsaw University, fi nds out when it was collected from there when it was transferred to the Belarusian State University, where it is located present tense In the story about the catalog of Karsky’s books, the author suggests that he was compiled during the Warsaw period of Karski’s life and activity, that his fi rst part was lost during the German occupation of Warsaw during the First World War. There are indications of what kind of books were in the library and the presence of autographs in the books.